Simulated dimensional compatibility of uncuffed and cuffed tracheal tubes for selective endobronchial intubation in children. Issue 2 (17th November 2020) - Moser, Berthold; Kemper, Michael; Dullenkopf, Alexander; Dave, Mital H.; Buehler, Philipp K.; Weiss, Markus
Abstract: Background: Cuffed tracheal tubes have recently been recommended for selective endobronchial intubation to establish single‐lung ventilation even in smaller children. This implies that, compared with uncuffed tracheal tubes, the cuffed tracheal tubes selected will be smaller and therefore have a shorter length. We hypothesized that cuffed tracheal tubes might be of insufficient length for selective endobronchial intubation if the tube cuff were fully immersed in the left or right mainstem bronchus. Methods: The distance from the proximal end of the tracheal tube to the upper border of the cuff in cuffed tracheal tubes and to the upper margin of the Murphy eye in uncuffed tracheal tubes, respectively, was assessed in sizes 3.0–7.0 mm internal diameter. The raw data sets of two previously performed studies obtained from 337 children aged from birth to 16 years, including the distances "teeth to tracheal tube tip" and "tracheal tube tip to carina, " were used to calculate age‐, weight‐, and height‐related data for the distance from "teeth to carina." Tracheal tube dimensions were compared with age‐related distances from "teeth to carina, " applying published recommendations for the selection of uncuffed and cuffed tracheal tubes for selective endobronchial intubation in children. Results: The differences between the length of the age‐related tracheal tube and the tracheal tube insertion length required to guarantee full insertion of the tracheal tube cuff or the Murphy eye within the mainstem bronchus ranged from −3.5 to 52.6 mm in cuffed tracheal tubes and from 42.3 to 83.3 mm in uncuffed tracheal tubes. Conclusions: For many age groups of patients requiring selective endobronchial intubation, the lengths of cuffed tracheal tubes, in contrast to those of uncuffed tracheal tubes, were revealed to be critically short for safe taping outside the oral cavity with the cuff placed completely within the right or left mainstem bronchus.